Decision-making and associative color learning in harnessed bumblebees (Bombus impatiens) (2012)
In honeybees, the conditioning of the proboscis extension response (PER) has provided a powerful tool to explore the mechanisms underlying olfactory learning and memory. Unfortunately, PER conditioning does not work well for visual stimuli in intact honeybees, and performance is improved only after antennal amputation, thus limiting the analysis of visual learning and multimodal integration. Here, we study visual learning using the PER protocol in harnessed bumblebees, which exhibit high levels of odor learning under restrained conditions. We trained bumblebees in a differential task in which two colors differed in their rewarding values. We recorded learning performance as well as response latency and accuracy.